Characterizing variations in ambient PM2.5 concentrations at the U.S. Embassy in Dhaka, Bangladesh using observations and the CMAQ modeling system. (1st March 2023) - Sarwar, Golam; Hogrefe, Christian; Henderson, Barron H.; Foley, Kristen; Mathur, Rohit; Murphy, Ben; Ahmed, Shoeb
Abstract: We analyze hourly PM2.5 (particles with an aerodynamic diameter of ≤2.5 μm) concentrations measured at the U.S. Embassy in Dhaka over the 2016–2021 time period and find that concentrations are seasonally dependent with the highest occurring in winter and the lowest in monsoon seasons. Mean winter PM2.5 concentrations reached ∼165–175 μg/m 3 while monsoon concentrations remained ∼30–35 μg/m 3 . Annual mean PM2.5 concentration reached ∼5–6 times greater than the Bangladesh annual PM2.5 standard of 15 μg/m 3 . The number of days exceeding the daily PM2.5 standard of 65 μg/m 3 in a year approached nearly 50%. Daily-mean PM2.5 concentrations remained elevated (>65 μg/m 3 ) for more than 80 consecutive days. Night-time concentrations were greater than daytime concentrations. The comparison of results obtained from the Community Multiscale Air Quality (CMAQ) model simulations over the Northern Hemisphere using 108-km horizontal grids with observed data suggests that the model can reproduce the seasonal variation of observed data but underpredicts observed PM2.5 in winter months with a normalized mean bias of -13 to –32%. In the model, organic aerosol is the largest component of PM2.5, of which secondary organic aerosol plays a dominant role. Transboundary pollution has a large impact on the modeled PM2.5 concentration in Dhaka, with an annual mean contribution of ∼40 μg/m 3 . Highlights: Daily mean PM2.5 level in Dhaka exceeds 65 μg/m 3 on 144 or more days per year. A pollution episode in Dhaka can persist for more than 80 consecutive days. Annual mean PM2.5 concentration in Dhaka can reach nearly 100 μg/m 3 . Organic aerosol is the largest component of PM2.5 in Dhaka. Annual mean contribution of transboundary pollution in Dhaka is ∼40 μg/m 3 .